Analisis Akad dalam Uang Elektronik - Nathisa Ismailiyya; Nourkholid Nourkholid (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Electronic money has become an easy way in the transaction process, for example Top Up e-toll, and transactions at agents who currently use the electronic money transaction system, besides that it also provides easy and fast services in carrying out transactions. The purpose of writing this article is to analyze the contracts contained in electronic money. Electronic money is a fairly new non-cash transaction device/instrument. Electronic money has several advantages compared to other electronic payment methods, namely prioritizing speed, comfort and skill in making payments. The method in this research uses qualitative methods. This qualitative research is used to understand and explain social phenomena in depth, emphasizing meaning and context. The data source obtained in this research comes from literature related to Electronic Money. The type of data taken uses qualitative data in the form of published sources or written narratives. The data analysis technique uses descriptive analysis to describe the research results that have been studied. Data collection techniques use literature studies sourced from articles and journals related to Electronic Money. Based on the results of the discussion from this research, it shows that in Electronic Money there are several contracts that are analyzed, including the Qordh, Wadi'ah, Ijarah, Wakalah Bilujroh, and Ju'alah contracts. In the changing times and technological innovation in all fields, especially financial aspects, have resulted in the existence of electronic money, in the era of globalization, the progress and development of these factors cannot be avoided, which has an impact on lifestyle and social interactions. One type of progress is society's need for micropayments